Upaya Peningkatan Pendapatan Petani Melalui Pemanfaatan Jamur Merang Menjadi Produk Olahan Di Kabupaten Karawang - Siti Nurlaela; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
The mushroom farmer group led by Mr. H. Sulaeman, is a farmer group that develops mushroom cultivation in Cirejag Village. Jatisari District, Karawang Regency. When the harvest arrives, there are problems that are often faced, namely, mushroom blooms are often found, the quality of the mushrooms that bloom is not in accordance with the quality of market demand. This causes the blooming mushrooms to be consumed personally or used as animal feed because farmers have not been able to process them into quality processed products. This product diversification effort is aimed at providing training on mushroom processing and marketing through E-commerce so as to maximize the profits obtained by mushroom farmers. The method used is in the form of training to farmer groups regarding post-harvest processing and how to market products through E-commerce. Currently the farmer group has been able to produce mushroom crackers with an initial production weight of 1,500gr to 13pcs raw crackers with a selling price of Rp. 9,000,- /pcs or 11pcs of fried crackers with a selling price of Rp. 15,000,-/pcs for the original taste and Rp. 16.000,-/pcs for other flavors with a weight of 100gr/pcs.